1993
DOI: 10.1016/0014-5793(93)81804-9
|View full text |Cite
|
Sign up to set email alerts
|

The 3′‐terminal untranslated region of alfalfa mosaic virus RNA 4 facilitates the RNA entry into translation in a cell‐free system

Abstract: In order to understand the role of the 3'-terminal untranslated region (3'-UTR) of alfalfa mosaic virus (AIMV) RNA 4 in viral RNA translation we have constructed the RNA derivatives differing in the length of their 3'-terminal portions and expressed them in a wheat germ extract. The result shows that the removal of the 3'-UTR from A1MV RNA 4 causes a lagged RNA translation in the cell-free system as compared with the translation of the full length RNA 4, thus suggesting the involvement of the 3'-UTR in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Examination of coat protein mRNA translation in vitro and in vivo revealed this mRNA to be efficiently translated even in the presence of large quantities of a cellular mRNA competitor. A functional role for the 3Ј UTR in coat protein mRNA translation was demonstrated by conducting similar experiments with mutant mRNAs lacking the 3Ј UTR; loss of the 3Ј UTR consistently reduced the efficiency of coat protein synthesis without altering mRNA stability (177,399). Interestingly, it was found that the 3Ј UTR was required for assembly of the coat protein mRNA into polyribosome complexes, indicating that the 3Ј UTR was an important determinant for ribosome binding (177).…”
Section: Vol 64 2000 Viral Gene Expression In Eukaryotes 251mentioning
confidence: 93%
See 1 more Smart Citation
“…Examination of coat protein mRNA translation in vitro and in vivo revealed this mRNA to be efficiently translated even in the presence of large quantities of a cellular mRNA competitor. A functional role for the 3Ј UTR in coat protein mRNA translation was demonstrated by conducting similar experiments with mutant mRNAs lacking the 3Ј UTR; loss of the 3Ј UTR consistently reduced the efficiency of coat protein synthesis without altering mRNA stability (177,399). Interestingly, it was found that the 3Ј UTR was required for assembly of the coat protein mRNA into polyribosome complexes, indicating that the 3Ј UTR was an important determinant for ribosome binding (177).…”
Section: Vol 64 2000 Viral Gene Expression In Eukaryotes 251mentioning
confidence: 93%
“…How, then, do AMV mRNAs adequately compete for available translation factors? Early evidence suggested that the 3Ј UTR of the AMV coat protein played a stimulatory role in mediating coat protein synthesis (399,496). Examination of coat protein mRNA translation in vitro and in vivo revealed this mRNA to be efficiently translated even in the presence of large quantities of a cellular mRNA competitor.…”
Section: Vol 64 2000 Viral Gene Expression In Eukaryotes 251mentioning
confidence: 99%
“…For example, a pseudoknot domain in the tobacco mosaic virus RNA 3Ј UTR may substitute for a poly(A) tail (14,17). In the case of AMV, Loesch-Fries et al reported that only diminished levels of coat protein were detected in Xenopus laevis oocytes injected with AMV CP RNA lacking the 3Ј UTR (50); moreover, in vitro translation experiments with fractionated wheat germ extracts suggested that the AMV CP RNA 3Ј UTR contributes to translational efficiency (64). These results suggested that the AMV CP RNA 3Ј UTR plays an important role in regulating CP RNA translation.…”
mentioning
confidence: 99%
“…The 3'-UTRs of several plant viral mRNAs were shown to increase their translational efficiency which was not correlated with the ability of 3'-UTR to stabilize and increase the half-life of mRNA molecules [2,8,11,23,24].…”
Section: Discussionmentioning
confidence: 99%